Biofabrication of a biomimetic supramolecular-polymer double network hydrogel for cartilage regeneration. (April 2020) - Li, Lan; Zhang, Kaijia; Wang, Tiankuo; Wang, Peng; Xue, Bin; Cao, Yi; Zhu, Liya; Jiang, Qing
Abstract: Cartilage injury is difficult to self-heal due to avascular microenvironment and special mechanical properties. These features challenge the design of tissue engineered cartilage and repairing effect. In this study, a supramolecular-polymer double network (DN) hydrogel was designed to estimate the cartilage regeneration capability. This consisted of self-assembly of peptides supramolecular networks and covalent polymer networks together, and the designed hydrogel demonstrated excellent mechanical properties with Young's modulus of ~209 kPa, the compression limit of it was >70%, the toughness was ~47 kJ m −3 and associated with fast recovery in seconds. Compared with single network hydrogel, this DN hydrogel exhibited better performance in cell viability and differentiation. A rabbit model of cartilage defect was employed to verify the effect of treatment as proof of principle. After 12 weeks' in vivo study, the cartilage defects were repaired significantly by biomimetic DN hydrogel. The native cartilage-like extracellular matrix (ECM) and cell arrangement were observed in the regenerated tissues. We anticipated that this hydrogel design might be a promising solution in artificial engineering of cartilage and other elastic tissues due to its excellent elasticity, toughness, fast recovery, stress unloading properties, and cartilage regenerative capability. Graphical abstract: Unlabelled Image Highlights: This DN hydrogel can mimic mechanical properties of native cartilage, including stiffness, toughness, and compression limit. The addition of HAMA can mimic the ECM of native cartilage, enhancing the biocompatibility and viscoelasticity. The outstanding biomechanical and biochemistry features of the DN hydrogel can notably improve the cartilage regeneration.